A Rare Case of Giant Neuroendocrine Tumor of the Thymus Treated with EN Bloc Resection - Fracasso, João Isidro; Albuquerque, Antônio Benincá; Rovani, André Luca Boeira; Maroni, Larissa; de Macedo, Guilherme Baroni; Priori, Leonardo; Dal'Maso, Vinícius Buaes; Simon, Tiago Teixeira; Braghini, Pedro Moacir Braghirolli; Beltrame, Cássia (International Journal of Innovative Research in Medical Science, 2019)
Neuroendocrine tumors (NETs) are epithelial neoplasms with predominant neuroendocrine differentiation that arise in most organs of the body. Neuroendocrine tumors of the thymus (tNET) and mediastinum are very uncommon. We report the case of a 49-year-old male patient with neuroendocrine tumor of the thymus, superiorly in the anterior mediastinum, asymptomatic of the respiratory tract presenting with epigastric pain, treated with the lesion's surgical resection en bloc associated with radiotherapy and chemotherapy.